Louise Westling. The Logos of the Living World: Merleau-Ponty, Animals, and Language. New York: Fordham UP, 2014. xiv + 187 pp. - Vera Coleman (Studies in 20th & 21st Century Literature, 2015)
Review of Louise Westling. The Logos of the Living World: Merleau-Ponty, Animals, and Language. New York: Fordham UP, 2014. xiv + 187 pp.
Keywords: Maurice Merleau-Ponty; critical animal studies; ecocriticism